A study of placental blood drainage in third stage of labour to prevent postpartum haemorrhage: a randomized controlled study - Bhongle, Jaya Kashinathrao; Agarwal, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: PPH is most common cause of maternal mortality accounting for 25-30% incidence and third stage of labour plays most crucial role in preventing postpartum haemorrhage. Methods: A prospective randomized control study in which 100 low risk pregnant women, admitted to labour ward with term gestation were evaluated. They were divided into 2 groups- control group (controlled cord traction) and study group (placental cord blood drainage), 50 pregnant women in each group. Duration of third stage and Amount of blood loss in third stage were evaluated and compared between the 2 groups. Results: Mean duration of third stage of labour in study group was 3.96±1.36 minutes and in control group was 6.00±2.12 minutes. The mean amount of blood loss in third stage of labour in study group was 99.80±56.47 ml in control group was 171.760±96.94 ml. Drop in haemoglobin level after delivery in control group was almost double than study group. Conclusions: Placental cord blood drainage in the management of third stage is non-invasive, easy, safe method which can be used in active management of third stage of labour as it has minimal interference in natural mechanism of placental separation. Placental cord blood drainage should be encouraged for management of third stage of labour universally to all pregnant women specifically in low resource setting areas.